Efeito do exercício físico em idosos com insuficiência cardíaca : revisão sistemática e metanálise de ensaios clínicos randomizados - Marin, Lilian (2013)
Heart failure ( HF) is a clinical syndrome that results from a structural or functional cardiac , increasingly common in the general population and more prevalent in the elderly disorder. Physical training in patients with HF has been increasingly studied, however there are different methods of prescribing physical exercise as well as controversies in the reported findings . Thus developed a systematic review with metaanalysis on the effects of physical exercise in the elderly with HF who underwent aerobic exercise vs. control group vs resistance exercise . control group and combined exercise vs . control group . The theoretical foundation presents the epidemiological and socioeconomic importance of IC and that this drove the development of studies to enable a remarkable evolution in the understanding of its pathophysiology, taking the last fifteen years the therapeutic innovations . We emphasize the rehabilitation or programmed physical activity as a method of therapeutic intervention. Intensities, duration of intervention and exercise modalities may have different action in the pathophysiology of HF